Traces of a Stative-Eventive Opposition in Ancient Egyptian. Rethinking Pseudoparticiple as Old Perfective - Oréal, Elsa (Zeitschrift für ägyptische Sprache und Altertumskunde, 2010)
Challenging the usual semantic characterisation of the “adjectival” or nfr sw predication, this paper shows that it originally functioned as a non-eventive, stative (vs. dynamic) predication rather than as an essential (vs. contigent) predication. Conversely, the traditional characterisation of the Pseudoparticiple with statal verbs as an alleged stative will be questioned. This study thus claims that the Pseudoparticiple was initially a V-S periphrastic conjugation specialized for dynamical/eventive predication, forming one and the same paradigm with the Old Perfective sDm + lexical subject (which is not a sDm=f). The real “stative” counterpart to this re-united Old Perfective paradigm appears to be the nfr sw predication. From a typological point of view, this suggests that the opposition between event and state may have played a crucial role in the Proto-Egyptian verbal system.